Implementation of the Budget Efficiency Policy for Foreign Direct Investment (FDI) Deconcentration Funds at the Investment and One-Stop Integrated Services Office of West Sumatra Province - Dhuhaira Ratu Hussein; Syamsir Syamsir (Darul Yasin Al Sys, 2026)
Public expenditure efficiency and foreign direct investment governance have received increasing scholarly attention; however, limited research has examined how budget-efficiency policies affect the implementation of FDI deconcentration programmes at the provincial level. This study aims to analyse policy implementation, supporting and inhibiting factors, and institutional strategies related to FDI deconcentration budget efficiency at the Investment and One-Stop Integrated Services Office of West Sumatra Province. A qualitative approach with a descriptive case-study design was employed, involving four key informants selected through purposive sampling. Data were collected through semi-structured interviews, non-participant observation, and document analysis, then analysed through data condensation, data display, and conclusion verification. The findings show that budget efficiency was implemented through online coordination, integrated field visits, activity prioritisation, and digital investment promotion. These measures helped maintain basic service continuity and relatively favourable investment performance; however, they also reduced direct supervision, weakened the verification of Investment Activity Reports, and increased reliance on informal communication. The study contributes to policy implementation and value-for-money literature by demonstrating that fiscal savings do not necessarily produce substantive efficiency when supervisory capacity and accountability mechanisms are weakened. The findings imply the need for selective performance-based budgeting, protected funding for high-risk supervision, and an integrated hybrid monitoring system to strengthen the effectiveness, accountability, and sustainability of provincial FDI deconcentration governance.